Influence of cane molasses inclusion to dairy cow diets during the transition period on rumen epithelial development - Miller, William F.; Titgemeyer, Evan C.; Nagaraja, Tiruvoor G.; Watanabe, Daniel H. M. [UNESP]; Felizari, Luana D. [UNESP]; Millen, Danilo D. [UNESP]; Smith, Zachary K.; Johnson, Bradley J. (MDPI, 2021)
The objective of this study was to evaluate the addition of cane molasses during a 60 day dry period on performance and metabolism of Holstein cows during prepartum and postpartum periods. For experiment 1, 26 primiparous and 28 multiparous cows were used. Upon freshening, all cows were offered a common lactation diet. For experiment 2, six multiparous cows fitted with rumen cannulas were used to measure performance and metabolism, following the same protocol as experiment 1. Ruminal propionate increased by 10% during both prepartum and postpartum periods; however, papillae area was greater for cows not fed molasses, and volatile fatty acids (VFA) absorption from the rumen was not increased, resulting in similar glucagon-like-peptide-2 receptor (GLP-2R) density. The improved dry matter intake, when molasses was added into prepartum diets, translated into increased milk yield and energy-corrected milk (ECM) in Experiment 1 only for multiparous cows. For experiment 2, the improvement on milk performance was also observed, where cows fed molasses had 18.5% greater ECM production. Feeding molasses during a 60 day dry period positively influenced transition cow performance, and it was not accompanied by changes in rumen morphometrics; however, this indicates enhanced adaptation by the rumen epithelium based on similar capabilities for VFA absorption.
Keywords: Adaptation; Molasses; Performance; Prepartum; Rumen